The only solution is revolution: the Spanish Confederación Nacional de Trabajo and the problem of unemployment in Republican Spain, 1931–1933. (4th July 2018) - Garner, Jason; Benclowicz, José
ABSTRACT: Although the Great Depression has been the subject of much research, focus normally centers on the impact instead of the tactics developed by working-class organizations to tackle the problems it caused, specifically unemployment. Recent research has sought to fill this gap, but numerous areas remain uncovered. This paper covers two of these: the situation in Spain and the reaction of anarcho-syndicalist union – the Confederación Nacional de Trabajo. Spain presents an anomalous case; a country that saw the replacement of a semi-fascist dictatorship by a democracy in the 1930s. Furthermore, the fact that the initial government of the Spanish Second Republic included the Socialists provides an opportunity of comparing and contrasting the positions and policies of reformist and revolutionary workers' organizations. The study is based on predominantly on articles appearing in the CNT newspaper Solidaridad Obrera . The conclusion reached is that for the CNT rising unemployment was a symptom of an irreversible trend in a failing capitalist system, which could only be solved by the revolutionary overthrow of that system. Nonetheless, the union had to present plausible solutions to ameliorate the conditions of the workers to attract the unemployed and thus, create a force strong enough to lead that revolutionary change.